The governance of Chinese charitable Trusts - Jing, Hui, 1990- (Cambridge, United Kingdom ; New York, NY : Cambridge University Press, 2023)
Legislators in China introduced the charitable trust model in 2016 with the passage of the Chinese Charity Law. They constructed a new legal framework for this model, in order to unlock the potential of trust institutions to further and develop charitable causes. This is the first English-language monograph exploring the governance of Chinese charitable trusts from the perspective of law and sociology. Through the application of doctrinal analysis and semi-structured qualitative interviews, this book reveals that China's particular political, social, and economic conditions are essential to understanding the legislated governance framework for charitable trusts and its implementation in practice. Embedded in China's unique institutional context, the governance of Chinese charitable trusts can only be fully understood in light of relevant law, administrative practice, and private actions taken by charitable trust parties.
Introduction -- Chinese charitable trusts as public law - private law hybrids -- Legal regulation -- Administrative regulation -- Contractual regulation -- Analysis and conclusion.
Title from publisher's bibliographic system (viewed on 30 Aug 2023).
Keywords: Charitable uses, trusts, and foundation -- China